Teaching as a Moral Act: Vivian Paley and a Manifesto of Children's Rights in the Early Childhood Classroom - Cooper, Patricia M (Schools (Chicago, Ill.), 2021)
The purpose of this essay is to propose a manifesto of young children's rights in the early childhood classroom based on Vivian Paley's many formal classroom investigations into children's thinking, learning, and social emotional development. Analysis establishes, first, Paley's license to speak for young children by positioning her in the only role to which she lays claim--schoolteacher. The distinguishing characteristic of Paley's teaching and writing, her psychological orientation towards children and teaching, is considered next as the foundation for her work in children's fantasy play, storytelling, and story acting. A focus on the social life of the classroom follows next, notably around the issue of differences among children and the sanctioned exclusion of some from play, friendship, and even teacher attention. Finally, the proposed manifesto encapsulates six rights of young children in school, from the curricular to the psychological, as a manifesto emblematic of Paley's belief in teaching as a moral act.